(n-1)(n+1)=n^2-1 则1*2*3=2^3-2 2*3*4=3^3-3 .则原式=2^3+3^3+4^3+...+(n+1)^3-2-3-4-...(n+1) 1^3+2^3+...+n^3=[n(n+1)/2]^2 所以2^3+3^3+4^3+...+(n+1)^3=[(n+1)(n+2)/2]^2-1 2+3+4+...+(n+1)=(2+n+1)n/2 所以原式=[(n+1)(n+2)/2]^2-1-(n+3)n/2
如何计算下题: 1×2×3+2×3×4+3×4×5+4×5×6+5×6×7+6×7×8+7×8×9+……+n×(n+1)
1个回答
相关问题
-
计算:1×2+2×3+3×4+4×5+5×6+6×7+7×8+8×9=______.
-
计算:1×2+2×3+3×4+4×5+5×6+6×7+7×8+8×9=______.
-
计算:1×2+2×3+3×4+4×5+5×6+6×7+7×8+8×9=______.
-
计算:1×2+2×3+3×4+4×5+5×6+6×7+7×8+8×9=______.
-
计算下列各题. 3×4+2= 4×3+5= 3×6+4= 8×9+7= 4×7-6= 2×9-8= 3×8-4= 4×9
-
急救1×3×5×7×9×11×…×(n-1)/2×4×6×8×…×n的极限.
-
1×2×3×4×5×6×7×8×9×10=???
-
1×2×3×4×5×6×7×8×9×10=
-
1+2+3+4+5+6+7+8+9+10×1×2×3×4×5×67×8×9×10=
-
计算:1×2×3×4×5×6×7-(1+2×1×2+3×1×2×3+…+6×1×2×3×4×5×6)=______.